THE MORAL IMPORTANCE OF DEVELOPING NATIONAL AND MARTIAL SPIRIT ON FUTURE RESERVE OFFICERS (Academicia Globe: Inderscience Research, 2023)
In this article the spiritual significance of the development of national and martial spirit among future reserve officers, the basic concepts of the philosophy of history in the era of romantic nationalism is highlighted, as well as the concept within the framework of ethnic nationalism, the main categories of the theory and practice of educational work, ideological and spiritual foundations aimed at constant attention to victory and the implementation of the spiritual foundations and principles of the serviceman, unit, association and armed forces.